1986
DOI: 10.1017/s0305004100064471
|View full text |Cite
|
Sign up to set email alerts
|

On Hammersley's minimum problem for a rolling sphere

Abstract: The problem posed by Hammersley (1983) of finding the shortest path along which a sphere can roll from one prescribed state to another is formulated by using quaternion calculus of variations and optimal control theory. This leads to a system of coupled nonlinear differential equations with prescribed end conditions. From the resulting expression for the curvature, it is shown that the differential equation of the required path in intrinsic coordinates is the same as the equation of motion of a simple pendulum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 1 publication
0
14
0
3
Order By: Relevance
“…Setting N = γ 2 − 1 A + γ K + γ 2 P , extending L to L 0 0 0 , and calculating the differentials using ( * ) gives: where the last line follows from Lemma 21,4). Now compute using Theorem 9, 1) and Lemma 21:…”
Section: Complete Integrabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Setting N = γ 2 − 1 A + γ K + γ 2 P , extending L to L 0 0 0 , and calculating the differentials using ( * ) gives: where the last line follows from Lemma 21,4). Now compute using Theorem 9, 1) and Lemma 21:…”
Section: Complete Integrabilitymentioning
confidence: 99%
“…The basic requirement is to determine the path of minimal length in E n traced by the point of contact of the sphere S n as it rolls without slipping from a given initial point x 0 ∈ E n to a prescribed terminal point x 1 ∈ E n and which also transfers a given initial rotational orientation of the sphere to some prescribed terminal orientation, where n ≥ 2. The case n = 2 has been studied in particular contexts by a variety of authors [4,6,12,14,18,21]. In [14], it is shown that the optimal curves are also solution curves for Euler's elastic problem, whereas [21] makes an interesting connection with a 1910 paper by Cartan and concludes that the symmetry algebra for the distribution of the rolling sphere is a noncompact real form of the exceptional Lie group G 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Позже А. Артур и Дж. Уолш получили уравнения для экстремальных траекторий в терминах кватернионов [2]. В. Джурджевич провел качественное исследование этих тра-екторий и показал, что при оптимальном качении точка контакта сферы и плоскости движется по эластикам Эйлера [3].…”
Section: и ю бесчастныйunclassified
“…А. Артурс и Дж. Уолш в [6] доказали, что уравнения для экстремальных траекторий в этой задаче интегрируемы в эллиптических функциях. В. Джарджевич в [7], [8] показал, что при оптимальном качении точка контакта сферы и плоскости движется по эластикам Эйлера (стационар-ным конфигурациям упругого стержня на плоскости; см.…”
Section: § 1 введениеunclassified